2016
DOI: 10.1186/s12880-016-0146-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation in type and frequency of diagnostic imaging during trauma care across multiple time points by patient insurance type

Abstract: BackgroundResearch has shown that uninsured patients receive fewer radiographic studies during trauma care, but less is known as to whether differences in care are present among other insurance groups or across different time points during hospitalization. Our objective was to examine the number of radiographic studies administered to a cohort of trauma patients over the entire hospital stay as well as during the first 24-hours of care.MethodsPatient data were obtained from an American College of Surgeons (ACS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…34 Patient race and insurance type influence the diagnostic workup received by patients in the ED, but it is unclear, again, whether this represents underuse or overuse of services. 35,36 Other studies have also demonstrated more intensive health service utilization, besides imaging, in the ED for patients who speak languages other than English, possibly in an effort to overcome diagnostic challenges posed by communication difficulties. 37,38…”
Section: Discussionmentioning
confidence: 99%
“…34 Patient race and insurance type influence the diagnostic workup received by patients in the ED, but it is unclear, again, whether this represents underuse or overuse of services. 35,36 Other studies have also demonstrated more intensive health service utilization, besides imaging, in the ED for patients who speak languages other than English, possibly in an effort to overcome diagnostic challenges posed by communication difficulties. 37,38…”
Section: Discussionmentioning
confidence: 99%
“…As noted, we observed relatively lower rates of inappropriate imaging among patients with an HMO plan, which is line with some literature suggesting these types of plans have in place more stringent pre-authorization requirements for expensive clinical services. 34,35 However, we did not have information regarding whether and how health plans reviewed specific claims included in the study. Based on discussions we have had with senior leaders of health insurance companies in Massachusetts, during the time frame covered by this study most orders for diagnostic imaging were required to undergo some form of pre-authorization review, but these review systems did not include the type of criteria that ACR guidelines entail and medical denial rates were very low.…”
Section: Discussionmentioning
confidence: 99%
“…HMO plans often feature pre-authorization requirements and related controls for expensive clinical services that some studies suggest influence utilization for imaging services. 34,35 For median household income, a proxy for a patient's financial resources for covering deductibles and co-pays connected with imaging procedures, we grouped patients by quartiles. For geographic location, we grouped patients based on whether their residence was located in the northeast, southeast, central, or western regions of the state as this may account for some differences in the availability of imaging technology.…”
Section: Variables and Measuresmentioning
confidence: 99%